Getting to Know Non-Fungible Tokens (NFT) and Decentralized Finance (DeFi) In The Era of Society 5.0 - Kadir, Syahruddin; RAH, Abdu Rahman; Yusuf, Nur Indri Andriyani (International Journal of Islamic Finance, 2023)
Background: In 2022 a student traded his selfies for a profit of 1.7 billion rupiah and managed to attract the attention of the world community. Objectives: This research aims to review the concepts of NFT and DeFi and to determine their utilization value. Novelty: Value of benefits (Maqashid Sharia) in NFT and DeFi Research Methodology / Design: The method used is a literature study with a phenomenological approach and the grand theory is analyzed using a constant comparison technique (qualitative). Findings: The research results explain that NFT is a digital work such as art, music, and photos that are traded using blockchain technology. DeFi is a financial ecosystem built by blockchain technology by providing financial services using cryptocurrency as an investment tool with easy and transparent access without being controlled by any financial institution. DeFi and NFT will build a more advanced financial industry by presenting decentralized financial services in the era of society 5.0. With just an internet connection and a compatible device, people can access various financial services without having to rely on account books, mobile banking, and so on. Implication: Its presence will open up new avenues for digital financial technology in the future. NFT and DeFi contain beneficial values in terms of maqashid sharia, namely hifzu al-din (protecting religion), hifzu al-'aql (protecting reason), hifzu al-nafs (protecting the soul), hifzu al-nasl (protecting offspring, and hifzu al-mal (protecting property).